Consumer Innovativeness Dan Consumer Attitude Dengan Self Congruity Sebagai Variabel Mediasi Pada Konsumen Green Skincare - Kristiningsih Kristiningsih; Sri Hartini; Indrianawati Usman (BALANCE: Economic, Business, Management and Accounting Journal, 2020)
Innovation is something that is important for businesses to survive in the era of competition. Innovation allows companies to continue to make and improve their offerings, and these offers can be implemented in business only if the customer considers the product to be innovative. This study aimed to examine the effect of consumer innovation on consumer attitudes with self-congruity as a mediating variable. The study was conducted on consumers of green skincare products in East Java. To test the hypothesis, a structural Equation Model analysis was performed using WARP PLS. The results showed that there was a positive influence between consumer innovativeness on self-congruity and consumer attitude. Kata kunci                  : consumer innovativeness, consumer attitude, self congruity